Robot dogs, interaction and ludic literacy: Exploring smart toy engagements in transgenerational play (Revista Lusófona de Educação, 2020)
This article highlights a study focusing on playful human-robotics interaction with an interest in robot dogs, technologically enhanced play, and ludic literacy. In order to find out how players of different ages react to, approach and employ a robot dog (called Golden Pup) in play, we designed an experimental study with 6–7-year-old preschool children and 80+-year-old seniors. We conducted the study with preschoolers and seniors, who during a playtest session interacted with a toy robot, namely a smart toy dog resembling a golden retriever puppy. Our aim was to find out how the toy robot invites playful interaction with it, facilitates social engagement between generations of players, and opens up conversations around social robotics and adaptive learning on toy-based technologies between players of different ages. Our findings suggest the role and importance of play in media education and show how robotic toys can be used to enhance ludic literacy when shared as a part of the transgenerational play.Keywords: human-computer interaction; ludic literacy; robotics; toy-based learning; transgenerational play.